Expansion of the Urban Area: The Fertilizers as one of the Challenges in the Coexistence of Rural and Urban Spaces. - Schimanski, Edina; M. Scheffer, Sandra; R. de Moura, Reidy (European Journal of Sustainable Development, 2014)
Abstract: This paper is part of a study carried out by researchers from the group of studies on environmental, gender and poverty issues, which is linked to the Applied Social Sciences Masters and Doctorate Program at Ponta Grossa State University. This is a qualitativequantitative study with characteristics of exploratory research, which addresses the social consequences of the use of fertilizers/pesticides to poor families living in the periphery of the city of Ponta Grossa in the South of Brazil. Triangulated data, obtained through field trips, interviews and participant observation, demonstrated the seriousness of the population contact with fertilizers. Theoretical studies on the theme identified that one of the most remarkable phenomena in the current Brazilian society is the speed of the urbanization process. Historically, the expansion of cities has been marked by the logics center-periphery, and in the last decades the transfer of groups of people has been noticed from the most central areas (due to economical and estate interests) to the most peripheral ones. It is important to consider the consequences of this phenomenon and how it is foreseen in the municipal planning, once it is in the rural-urban where the most significant natural resources are found, those which are vital to both the environmental balance and urban infra-structure systems. In the region of Ponta Grossa, Paraná State, South of Brazil, a process of strong junction between rural and urban has been observed. The evidence is that several areas and entire communities have developed very close to large areas of soybean, corn, wheat and other crops and thus, are totally exposed to the fertilizers used in those areas. Data collected also shows that the families living in those areas experience a routine of severe environmental, social and health problems without really understanding how serious this problem is. Key words: urban expansion, urban-rural relationship, agricultural / community implication